Ducey, John. Interview with John Ducey - Millar, Edward (2012)
John Ducey discussing his store; contents of the store; store use; wood gathering and storage; darts; lobster pots; lobster buoys; repairing and preparing crab and lobster pots; shift to bio-degradeable twine for crab pots in 2013; coloring of lobster buoys for identification; ghost pots and ghost nets